Schools in church history (Cambridge University Press)
Published for The Ecclesiastical History Society, Cambridge. NEW TO CAMBRIDGE IN 2016 Studies in Church History is an annually published series comprising papers and communications delivered at the Ecclesiastical History Society?s conferences. Each volume presents important new work, by established as well as new scholars, on a particular theme. Volumes are available to members of the society at a reduced price.
Keywords: Religion